A NanoSIMS Investigation on Timescales Recorded in Volcanic Quartz From the Silicic Chon Aike Province (Patagonia) - Seitz, Susanne; Putlitz, Benita; Baumgartner, Lukas; Meibom, Anders; Escrig, Stéphane; Bouvier, Anne-Sophie (Frontiers in Earth Science, 2018)
We compare quartz zonation and diffusion timescales of crystal-rich rhyolitic ignimbrites and crystal-poor rhyolitic lava flows from the Jurassic Chon Aike Province as exposed in Patagonia (Argentina). The timescales are assessed by using diffusion modelling based on nanoscale secondary ion mass spectrometry (NanoSIMS) analysis of titanium (Ti) concentration profiles in quartz crystals oriented by image analysis using micro-tomography. Quantitative Ti-data were acquired by SIMS to estimate crystallization temperatures. The textural and geochemical analysis revealed clear differences between crystal-poor rhyolitic lava flows and crystal-rich rhyolitic ignimbrites. Quartz crystals from rhyolitic lava flows display simple oscillatory cathodoluminescence (CL) zoning interpreted to be magmatic and diffusion chronometry suggest a short timescale for quartz crystallization from 5.6 ± 2.2 yr to 41.6 ± 9.8 yr. Resorption textures are rare, and hence crystals in rhyolitic lava flows recorded a simple, rapid extraction, transport and eruption history for these crystal-poor melts. Rhyolitic ignimbrites, in contrast, reveal complex zoning patterns, reflecting several episodes of partial resorption and growth throughout their crystallization history. The complex quartz zoning textures together with longer diffusion times (< 350 yr), rather suggest a storage in a mush with fluctuating pressure and temperature conditions leading to intermittent resorption. Yet, a final quartz overgrowth rim occurred over a much shorter timescale in the order of years (< 3 yr), which implies that crystal-rich ignimbrites can be re-mobilized very fast.